Kinetics of Photodegradation and Durability of Inkjet Prints: A Comparative Study of Aqueous Solutions and Printed Substrates - Barbara Blaznik; Franci Kovač; Sabina Bračko (Molecules)
The durability of the materials is often limited as they fade under the influence of external factors, particularly light. The present research aimed to study the photodegradation of commercial inkjet inks in an aqueous solution. The results were compared with their stability on prints in order to establish the connection between the kinetics of photodegradation of dye in the solution and the durability of the final print. Thin-layer chromatography (TLC), chromatography with a mass selective detector (GC/MS), and spectrophotometric measurements were used to study the effect of light, including near UV. The results clearly show that the catalytic effect between different dyes cannot be avoided, as the inks for inkjet printing are usually a mixture of different colorants. A comparison of the results of photodegradation of the dye in solution and on the final prints does not show a direct connection due to the different influences of external factors. Consequently, it was established that it is not possible to predict the photodegradation of prints solely based on a single dye’s analysis in solution. The paper as a substrate must be included in the analysis, as it significantly influences the photodegradation of the print.